1999
DOI: 10.1073/pnas.96.19.10711
|View full text |Cite
|
Sign up to set email alerts
|

Marrow stromal cells migrate throughout forebrain and cerebellum, and they differentiate into astrocytes after injection into neonatal mouse brains

Abstract: Stem cells are a valuable resource for treating disease, but limited access to stem cells from tissues such as brain restricts their utility. Here, we injected marrow stromal cells (MSCs) into the lateral ventricle of neonatal mice and asked whether these multipotential mesenchymal progenitors from bone marrow can adopt neural cell fates when exposed to the brain microenvironment. By 12 days postinjection, MSCs migrated throughout the forebrain and cerebellum without disruption to the host brain architecture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
953
3
22

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,476 publications
(1,009 citation statements)
references
References 36 publications
15
953
3
22
Order By: Relevance
“…Previous in vivo studies have examined the differentiation of murine MSC. Transplantation of murine MSCs gave rise to neurons (8,29,35) and astrocytes (29). Two recent reports have shown that human MSCs could differentiate in vitro into neurons (49,57) and astrocytes (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vivo studies have examined the differentiation of murine MSC. Transplantation of murine MSCs gave rise to neurons (8,29,35) and astrocytes (29). Two recent reports have shown that human MSCs could differentiate in vitro into neurons (49,57) and astrocytes (49).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow stromal cells or mesenchymal stem cells (MSCs) not only give rise to mesodermal lineage cells such as osteoblasts, chondrocytes, adipocytes, and muscle cells (4,13,29,55,33), but also adopt neuroectodermal cell fate. It has been shown that donor-derived neurons and astrocytes are found in host rodent brain following transplantation of rodent bone marrow (8,14,29,35). However, it is not known if transplantation of MSCs into the brain can be beneficial in treating neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, they differentiated in vivo into astrocytes and even neurons. 47,48 Human MSCs were injected into rats after middle cerebral artery occlusion. 49,50 In both studies, implanted cells reduced the lesion volume and elicited functional improvement compared with the control sham group.…”
Section: Stem Cells In Cnsmentioning
confidence: 99%
“…14 Marrow stromal cells (MSCs) normally give rise to bone, cartilage, and mesenchymal cells (reviewed in La Russa et al 15 ). Isolation of MSCs that can differentiate to brain cells, such as glial cells 16 and neural cells, 17 has been demonstrated. Infusion of human MSCs into rat striatum resulted in engrafting, migration, and survival of the cells.…”
mentioning
confidence: 99%